Coastal environment-based rotating wheel media to increase motivation and critical thinking of elementary school students - Slamet Rohani; Nadi Suprapto; Suryanti Suryanti; Nafi Isbadrianingtyas (Universitas Kanjuruhan Malang, 2026)
This study aims to develop a Coastal Environment-Based Rotating Wheel media in the learning of Science on the Five Senses material to develop learning motivation and critical thinking skills of third-grade elementary school students. This study uses the Research and Development method, the ADDIE model, and a quasi-experimental design in the experimental and control classes. The research subjects were 60 students. Data collection techniques used questionnaires and tests. Based on the results of the validity test, the overall average score was 82.33% in the valid category, the practicality test was 88.97% in the very practical category, and the effectiveness test of the percentage of motivation was 90.81% in the very high category. The score on the t-test had a significance value of 0.00 where 0.00 <0.05 so that Ha was accepted and Ho was rejected. So it was concluded that the media met the criteria of valid, practical and effective.